2006
DOI: 10.1051/0004-6361:20054185
|View full text |Cite
|
Sign up to set email alerts
|

The Supernova Legacy Survey: measurement of $\Omega_{\mathsf{M}}$, $\Omega_\mathsf{\Lambda}$ andwfrom the first year data set

Abstract: We present distance measurements to 71 high redshift type Ia supernovae discovered during the first year of the 5-year Supernova Legacy Survey (SNLS). These events were detected and their multi-color light-curves measured using the MegaPrime/MegaCam instrument at the Canada-France-Hawaii Telescope (CFHT), by repeatedly imaging four one-square degree fields in four bands, as part of the CFHT Legacy Survey (CFHTLS). Follow-up spectroscopy was performed at the VLT, Gemini and Keck telescopes to confirm the nature… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

71
1,370
5
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,228 publications
(1,475 citation statements)
references
References 61 publications
71
1,370
5
7
Order By: Relevance
“…The largest high-redshift (z ≈ 0.4 − 1.0) data sets are those from the ESSENCE survey (Wood-Vasey et al 2007; Narayan et al, in prep. ; ∼200 spectroscopically confirmed Type Ia SNe) and the CFHT Supernova Legacy Survey (SNLS; Astier et al 2006;Conley et al 2011;Sullivan et al 2011; ∼500 spectroscopically confirmed Type Ia SNe in the three-year data set SNLS3). At very high redshifts, HST surveys (Riess et al, 2004Suzuki et al, 2012) have yielded ∼ 25 Type Ia SNe at z > 1.0, which confirm the expectation that the universe was decelerating at high redshift and limit possible systematic effects from evolution of the supernova population or intergalactic dust extinction.…”
Section: The Current State Of Playmentioning
confidence: 99%
“…The largest high-redshift (z ≈ 0.4 − 1.0) data sets are those from the ESSENCE survey (Wood-Vasey et al 2007; Narayan et al, in prep. ; ∼200 spectroscopically confirmed Type Ia SNe) and the CFHT Supernova Legacy Survey (SNLS; Astier et al 2006;Conley et al 2011;Sullivan et al 2011; ∼500 spectroscopically confirmed Type Ia SNe in the three-year data set SNLS3). At very high redshifts, HST surveys (Riess et al, 2004Suzuki et al, 2012) have yielded ∼ 25 Type Ia SNe at z > 1.0, which confirm the expectation that the universe was decelerating at high redshift and limit possible systematic effects from evolution of the supernova population or intergalactic dust extinction.…”
Section: The Current State Of Playmentioning
confidence: 99%
“…10 −3 eV [1][2][3][4][5][6][7][8][9][10][11]. The same measurements allow for the suggestive interpretation of dark energy as a small but non-vanishing pure vacuum energy: the famous cosmological constant, for which w = −1 must hold at all times.…”
Section: /4mentioning
confidence: 99%
“…For example, the 2005 Sloan Digital Sky Survey II (SDSS) supernova program generated approximately 4,000 objects per night which needed to be visually checked by humans for verification [16]. The ESSENCE and SuperNova Legacy Survey (SNLS) supernova searches both resulted in 100-200 objects to scan per night with a significantly smaller input data load than the SNfactory [17]. Techniques used in these surveys will not scale to future, much larger data sets.…”
Section: Related Workmentioning
confidence: 99%
“…In 2005, the SNfactory pioneered the use of machine learning algorithms to replace "cuts" for supernova object detection [9], and since then, such techniques have been utilized by other supernova searches, including SDSS and SNLS [16,17]. The SDSS "autoscanner" uses a combination of heuristics and a naive Bayes classifier to filter out non-SN objects, but they do not provide a comparison of the efficacy of any other types of machine learning algorithms for supernova search.…”
Section: Related Workmentioning
confidence: 99%